Evolution of admitted patients with advanced cirrhosis of the liver to the emergency service for adults from a third level hospital - Saravia-Atúncar, Andrés V. (2019)
Objective. To determine the evolution of patients with advanced liver cirrhosis after being admitted to the emergency ward of a tertiary hospital and identify associated factors to mortality at six months of follow up. Material and methods. A retrospective and observational study was carried out in patients older than 18 year-old with advanced liver cirrhosis (Child-Pugh C stage) admitted to the emergency ward in a tertiary hospital, from February to August of 2017. Medical reports, clinical history and computerized files (follow-up at 12 months) were reviewed. A bivariate statistical analysis was applied using SPSS 24 and according to ethical principles.Results. We identified 83 cases, with an average age of 68 year-old (± 9.5), male 52%; 22% alcoholic and 6% viral etiology. Nineteen (23%) patients died on first admission to emergency ward, 61% at three months, 73% at 6 months and 81% at 12 months of followup. The most frequent causes of admissions were infection, gastrointestinal bleeding, encephalopathy and ascites, with an average stay of 5-day in the emergency ward. And, 46% of patients returned to emergency ward (ambulatory) and 68% were readmitted during the study period. Three patients (3,6%) underwent liver transplant who survived during the follow-up. When comparing mortality at 6 months, it was obtained p < 0,05 with bilirubinemia, albuminemia, index MELD and MELD-sodium. Conclusions. Patients with advanced liver cirrhosis admitted to emergency ward had high mortality in the short and medium follow up. The associated factors were liver transplantation, bilirubinemia, albuminemia, MELD and MELD-sodium high scores.